The gender difference in distance running performance has plateaued: an analysis of world rankings from 1980 to 1996 - Sparling, P. B.; O'Donnell, E. M.; Snow, T. K. (Medicine & Science in Sports & Exercise, 1998)
PURPOSE: Annual world rankings from 1980-1996 were used i) to determine if the gender difference in distance running events has stabilized, and ii) to examine whether the relative decline in pace as race distance increases is different between men and women. World best (WB) and 100th best times in the 1500 m and the marathon (42 km) for each of the 17 years were the indices used to represent overall trends in men's vis-a-vis women's distance running. METHODS: These data were analyzed using regression analyses to develop and compare gender-specific equations. In the 1500 m, the gender difference in WB times (11.1 +/- 1.1%) was consistent from 1980 to 1996, and the slight rate of improvement in event depth (i.e., 100th rankings) was similar for men and women. RESULTS: In the marathon, the gender difference in WB times (11.2 +/- 0.9%) was essentially the same as for the 1500 m. In 1980, the marathon was a fairly new event for the women, having only just been sanctioned by the International Amateur Athletics Federation (IAAF). As a consequence, the depth of the field increased quickly from 1980 to 1984. Since the mid-1980s, the rate of improvement for women in 100th-ranked times has leveled off to equal that of men. The average declines in relative pace for men and women from the 1500 m to the 10 km to the marathon were found to be remarkably similar with no diminishing of the gender difference as race distance increased. CONCLUSIONS: Based on worldwide indices of competitive distance running, the gender difference in distance running performance has plateaued in recent years. Concomitantly, over the past decade, opportunities for women to train and compete have approached parity with those of men. It is likely that the current gender difference in performance will remain fairly constant because of biological differences between men and women that give men an advantage in distance running.